Salvianolate ameliorates oxidative stress and podocyte injury through modulation of NOX4 activity in db/db mice. Issue 2 (17th December 2020) - Liang, Yiran; Liu, Hong; Fang, Yi; Lin, Pan; Lu, Zhihui; Zhang, Pan; Jiao, Xiaoyan; Teng, Jie; Ding, Xiaoqiang; Dai, Yan
Abstract: Podocyte injury is associated with albuminuria and the progression of diabetic nephropathy (DN). NADPH oxidase 4 (NOX4) is the main source of reactive oxygen species (ROS) in the kidney and NOX4 is up‐regulated in podocytes in response to high glucose. In the present study, the effects of Salvianolate on DN and its underlying mechanisms were investigated in diabetic db/db mice and human podocytes. We confirmed that the Salvianolate administration exhibited similar beneficial effects as the NOX1/NOX4 inhibitor GKT137831 treated diabetic mice, as reflected by attenuated albuminuria, reduced podocyte loss and mesangial matrix accumulation. We further observed that Salvianolate attenuated the increase of Nox4 protein, NOX4‐based NADPH oxidase activity and restored podocyte loss in the diabetic kidney. In human podocytes, NOX4 was predominantly localized to mitochondria and Sal B treatment blocked HG‐induced mitochondrial NOX4 derived superoxide generation and thereby ameliorating podocyte apoptosis, which can be abrogated by AMPK knockdown. Therefore, our results suggest that Sal B possesses the reno‐protective capabilities in part through AMPK‐mediated control of NOX4 expression. Taken together, our results identify that Salvianolate could prevent glucose‐induced oxidative podocyte injury through modulation of NOX4 activity in DN and have a novel therapeutic potential for DN.